Armenia Country Economic Update, Winter 2019 : A Strong Mandate for Change Amid a Global Slowdown - World Bank Group (World Bank, Washington, DC, 2019)
Following an initial spike in early 2018, Armenia’s economic performance slowed during the rest of the year, but still estimated to have above 5 percent growth for the year. Inflationary pressures remained low, while the external balances deteriorated. The overperformance of the fiscal accounts reflected strong revenue collection, sound control over current spending, and underperformance of capital expenditure. The outlook, however, is more conservative.